Nanoscale characterisation of grain boundary oxidation in cold-worked stainless steels - Kruska, K.; Lozano-Perez, S.; Saxey, David; Terachi, T.; Yamada, T.; Smith, G. (2012)
Atom-probe tomography was employed to characterise specimens containing the oxidised part of a grain boundary from a 304 stainless steel coupon specimen exposed to simulated PWR primary water. A TEM foil containing part of the same oxidised grain boundary was also extracted and characterised for comparison. Surface and grain boundary oxide compositions were identified and Ni enrichment was observed around the oxides. The data provides novel information on the role of the minor impurities and the formation of early-stage oxides. These studies were conducted as part of a broader investigation of the mechanisms underlying stress corrosion cracking in stainless steels.